Draft Genome Sequence of “Candidatus Nardonella dryophthoridicola” Strain NARMHE1, Endosymbiont of Metamasius hemipterus (Coleoptera, Curculionidae, Dryophthorinae) - Palmieri, Luciano; Pavarini, Ronaldo [UNESP]; Sharma, Prashant P. (American Society for Microbiology, 2022)
Here, we report the draft genome and annotation of “Candidatus Nardonella dryophthoridicola” strain NARMHE1, obtained via Oxford Nanopore sequencing of the ovaries of its host, the weevil Metamasius hemipterus, from a population from southeast Brazil.